2018
DOI: 10.1007/s10474-018-0800-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of selection principles in the study of the properties of function spaces

Abstract: For a Tychonoff space X, we denote by C p (X) the space of all real-valued continuous functions on X with the topology of pointwise convergence.In this paper we prove that:• if every finite power of X is Lindelëof then C p (X) to be strongly sequentially separable iff X is γ-set.• B α (X) -functions Baire class α (1 < α ≤ ω 1 ) on a Tychonoff space X with the pointwise topology -to be sequentially separable iff there exists a Baire isomorphism class α from a space X onto a σ-set.• B α (X) is strongly sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Let X be a set Y with the topology of Sorgenfrey line. Then the space X such that X satisfies S 1 (Ω ω cz , Γ) and iw(X) = ℵ 0 , but X 2 is not Lindelöf (Theorem 6.1 in [15]). Since Γ ω cz ⊂ Ω ω cz , by Proposition 8.4, X projectively S 1 (Ω, Ω).…”
Section: The Projectively S 1 (ω ω)mentioning
confidence: 99%
“…Let X be a set Y with the topology of Sorgenfrey line. Then the space X such that X satisfies S 1 (Ω ω cz , Γ) and iw(X) = ℵ 0 , but X 2 is not Lindelöf (Theorem 6.1 in [15]). Since Γ ω cz ⊂ Ω ω cz , by Proposition 8.4, X projectively S 1 (Ω, Ω).…”
Section: The Projectively S 1 (ω ω)mentioning
confidence: 99%
“…In the papers [2,3,6,16,[22][23][24][25][26]32] various selection principles for a Tychonoff space X were related to the selection principles for C p (X). Likewise, in [10,17,26,30,31] various selection games for X and C p (X) and a bitopological space (C(X), τ k , τ p ) were related.…”
Section: Theorem 43 ([20]mentioning
confidence: 99%
“…In a series of papers it was demonstrated that γ-covers, Borel covers, k-covers play a key role in function spaces ( [5,8,9,10,12,13,15,17,18,19,20,21,22] and many others). We continue to investigate applications of k-covers in function spaces with the compact-open topology.…”
Section: Main Definitions and Notationmentioning
confidence: 99%